(untitled) (Damu Journal of Sport Sciences, 2025)
prepare exercises using the alternating training method to develop performance endurance and some basic skills for indoor soccer players, and to identify the effect of the alternating training method to develop performance endurance and some basic skills for the individuals in the research sample. To achieve the goal, the researcher used the experimental method with a pre- and post-test to suit it with the research problem. The research population consisted of players from Baghdad clubs participating in the Iraqi Premier Futsal League for the season (2023 - 2024), which numbered (6) clubs, as the sample was chosen intentionally, and they were club players. (Science and Technology), numbering (20) players (12) players were chosen to represent the main experiment sample after randomly excluding (4) players as a survey sample, as well as excluding (3) goalkeepers. Thus, the sample will represent (18.18%) of the research population, The researcher conducted the pre- and post-test for individuals. The research sample, and appropriate statistical treatments were conducte), The researcher concluded that the training curriculum prepared in an alternating training style with matches and relaxation and calm-down exercises has proven effective in developing performance endurance and some basic skills in futsal football, and that the development of performance endurance has an impact in developing some basic skills in futsal football. The researcher recommends making sure to use the training curriculum using the alternating training method to develop performance endurance and some basic skills in indoor football, as well as making sure to take into account the use of other training methods that make the player more interesting and effective as a result of the diversity in training, and adopting the training curriculum used in the alternating training method in indoor football.